Pedagogical Process to Generate Community Learning Through the Participatory Design of a Board Game - Torres, Karoline Zuleyka; Vargas-Agüero, Fiorella (Revista Electrónica Educare, 2025)
Introduction. Didactic games constitute a powerful tool in both formal and non-formal educational contexts. This study implements a general pedagogical process based on the participative design of a didactic board game to facilitate an educational environment for community learning. Methods. Eighteen elderly individuals experiencing homelessness volunteered to participate in the study, all of whom were users of the shelter Centro Dormitorio Municipal San José in Costa Rica. The research employed interviews, dialogue circles, mental maps, brainstorm circles, and checkpoints. To ensure the transparency of the study, participants validated all information during evaluation sessions throughout the research process. Data collection techniques entailed a field diary and participant observation, supplemented by data categorization through the creation of matrices and classification based on similarities that were approved and evaluated by participants and later used in the creation of the board game. Participants worked together, along with researchers, to design a board game during weekly meetings held over a 1.6-year period. During this period, a pedagogical process was proposed that consisted of five phases (diagnosis, testing, creation, application and improvement, and dissemination); they are adaptable to diverse educational environments. Results. The board game potentialized three socio-emotional abilities identified as needs for this elderly population during the study: self-regulation, self-motivation, and self-knowledge. These elements were vital for participant engagement and for establishing significance in the learning experience, adding intention to the design and consciousness to the pedagogical process. Discussion. A holistic vision in our approach and methodology was vital for achieving the universal reach expected from the pedagogical process developed in this study. Here, we present a process that can be applied in diverse contexts to achieve the participatory creative design of a didactic board game and create opportunities for community learning.